Boswellia carterii oleoresin extracts induce caspase-mediated apoptosis and G1 cell cycle arrest in human leukaemia subtypes - Jones, Matthew Allan; Borun, Anna; Greensmith, David James (Frontiers in Pharmacology, 2023)
Leukemias are a common cancer in adults and children. While existing treatments are effective, they are associated with severe side-effects compounded by the emergence of drug resistance. This necessitates the need to develop new drugs and phytopharmaceuticals offer a largely untapped source. Oleoresins produced by plants in the genus Boswellia have been used for centuries in traditional medicine and recent work suggests they may exhibit anti-cancer activity. However, the underlying mechanisms remain unclear and most existing research focusses on Boswellia serrata; just one of many species in the Boswellia genus. To address these limitations, we elucidated the anti-cancer potential and associated mechanisms of action of Boswellia carterii.A methanolic solvent extraction method was optimised. The effect of methanolic extracts of Boswellia carterii on leukaemia (K562, MOLT-4 and CCRF-CEM) and normal (PBMC) cell line viability was assessed using MTT assay and flow cytometry. Cell morphology, apoptosis (Annexin-V/propidium iodide), mitochondrial membrane potential (Rhodamine-123) and the cell cycle (propidium iodide) were evaluated using flow cytometry. Regulatory protein expression was quantified using Western Blot.Methanolic extracts of Boswellia carterii oleoresin reduced the viability of K562, MOLT-4 and CCRF-CEM cell lines with selectivity indexes of between 1.75 and 2.68. Extracts increased the proportion of cells in late apoptosis by 285.4 ± 51.6 %. Mitochondrial membrane potential was decreased by 41 ± 2 % and the expression of cleaved caspase-3, -7 and -9 was increased by 5.7, 3.3 and 1.5-fold respectively. Extracts increased the proportion of cells in subG1 and G1 phase by 867.8 ± 122.9 % and 14.0 ± 5.5 and decreased those in S phase and G2/M by 63.4 ± 2.0 and 57.6 ± 5.3 %. Expression of CDK2, CDK6, cyclin D1 and cyclin D3 were decreased by 2.8, 4.9, 3.9 and 2.5-fold.We are the first to report that methanolic extracts of B. carterii are selectively cytotoxic against three leukemia cell lines. Cytotoxic mechanisms likely include activation of the intrinsic apoptotic pathway and cell cycle arrest through downregulation of CDK2, CDK6, cyclin D1 and cyclin D3. Our findings suggest that Boswellia carterii may be an important source of novel chemotherapeutic drugs and justifies further investigation.